PEDF attenuates insulin-dependent molecular pathways of glucose homeostasis in skeletal myocytes. (15th February 2016) - Carnagarin, Revathy; Dharmarajan, Arun M.; Dass, Crispin R.
Abstract: Pigment epithelium-derived factor (PEDF) is an anti-angiogenic serpin associated with insulin resistance in metabolic disorders such as diabetes, metabolic syndrome, obesity and polycystic ovarian syndrome. While the mechanism of PEDF induced-insulin resistance of metabolic disorders has been attributed to its inflammatory and lipolytic effects, little evidence exists to support a direct role of PEDF in mediating insulin resistance. Here, we seminally provide evidence that PEDF can inhibit insulin signal transduction governing glucose homeostasis from the receptor to the effector phosphorylation through Akt/PKB-dependent and -independent pathways in mouse and human skeletal muscle cell lines. PEDF attenuates the insulin-dependent molecular axes of glucose metabolism. Exposure of skeletal myocytes to PEDF attenuates insulin-dependent insulin receptor autophosphorylation, tyrosine phosphorylation of insulin receptor substrate 1, and dual loop phosphorylation-activation of Akt. PEDF significantly inhibits the downstream effector - glycogen synthase kinase (and thereby the glycogenic axis of insulin signalling). PEDF turned off both the molecular switches of GLUT4 translocation: IRS-Akt/PKB-AS160 mediated and IR-pCbl-dependent GLUT4 translocation (the molecular axis of glucose uptake). These findings implicate a direct effect of PEDF on multiple insulin-dependent molecular mechanisms of glucose homeostasis in skeletal muscle cells, thereby enabling it to contribute to peripheral insulin resistance at the cellular level. Graphical abstract: Highlights: PEDF is evolving as a protein of metabolic dysregulation. PEDF attenuates critical signalling pathways involved in insulin-dependent glucose homeostasis. PEDF could serve as a potential therapeutic target to handle the insulin resistance of metabolic disorders.